Height reduction in 539 tall girls treated with three different dosages of ethinyloestradiol. Issue 11 (November 1991) - Normann, E K; Trygstad, O; Larsen, S; Dahl-Jørgensen, K
Abstract : During the period 1970 to 1985, 539 constitutionally tall girls were treated with ethinyloestradiol in varying dosages to reduce final height. They all had a predicted final height above 181 cm (greater than +2.5 SD). The girls were all healthy and were treated with three different dosages of ethinyloestradiol. Throughout these 15 years recommended treatment regimens changed, and the treatments described followed these guidelines. Girls in group 1 (n = 263) were treated with 0.5 mg of ethinyloestradiol, group 2 (n = 178) with 0.25 mg, and group 3 (n = 98) with 0.1 mg. The total mean (SEM) reduction of final height was 5.9 (0.2), 5.3 (0.1), and 4.4 (0.2) cm when treated with 0.5, 0.25, and 0.1 mg respectively. Group 1 was treated for 2.02 (0.03) years and group 2 and 3 for 1.85 (0.04) and 1.63 (0.05) years respectively. When expressed in relation to the treatment period the reduction of final height was 3.0 (0.1), 3.1 (0.1), and 2.9 (0.2) cm/year of treatment respectively. All the girls were treated with ethinyloestradiol as a daily single dose, while progestogen was given daily the first 10 days of every month. In conclusion we found that a daily dose of ethinyloestradiol 0.1 mg for about 20 months is sufficient to reduce final height. We recommend starting treatment at a bone age of about 12 years.